A Survey of Forensic Analysis and Information Visualization Approach for Instant Messaging Applications - Shahnaz Pirzada, Shahnaz Pirzada; Ab Rahman, Nurul Hidayah; Niken Dwi Wahyu Cahyani, Niken Dwi Wahyu Cahyani; Othman, Muhammad Fakri (ijacsa, 2023)
Instant messaging applications, including WhatsApp, Viber, and WeChat, are moving beyond text messages to videos and voice calls, which are proportioned to current media, files, and locations. In this study, we surveyed existing forensic visualization and forensic analysis techniques for instant messaging applications, with the aim of contributing to the knowledge in the discussion of these research issues. A total of 61 publications were reviewed after searching various academic databases, including the IEEE, ACM Digital Library, Google Scholar, and Science Direct during the last five years. Our observation from research trends indicates that both forensic analysis and information visualization are relatively mature research areas. However, there is a growing interest in forensic visualization and automated IM forensic analysis. We also identified the lack of discussion on forensic selection criteria in existing forensic visualization works and the needs of benchmarking the evaluation method of automate forensic analysis tools.